The scholars' companion and ball-room vade mecum, comprising a description of all the principal dances ... With hints and instructions respecting toilet, deportment, &c., &c. ... - Hillgrove, Thomas (New York, T. R. Turnbull & Co., Printers, 1857)
This manual was reissued in 1858 under the title Hillgrove's scholars' companion and ball-room guide ..., and formed the basis for a similar publication, A complete practical guide to the art of dancing, published in 1863. Typical of many nineteenth-century dance manuals, little of the text originated from the pen of New York dancing master Thomas Hillgrove. Instead, much is borrowed from previously published manuals. The scholars' companion gives information on dress, introductions, etiquette and deportment and describes the most popular ballroom dances of the day--quadrille, waltz, polka, schottisch, polka redowa, polka mazurka, gorlitza, and redowa. Noticeably missing from Hillgrove's manual is any reference to the popular group dance known as the cotillon or German.
Available also through the Library of Congress Web site as facsimile page images and full text.
Keywords: Ballroom dancing -- Handbooks, manuals, etc; Dance Instruction and Technical Manuals